Cognitive assessment in excessive daytime sleepiness : Electrophysiological study - Legaa Ali Mohammad Elmekkawy; Eman Ahmed Maher; Mona Mohamed Abdelmonem Nada; Mye Ali Basheer (Cairo : Leqaa Ali Mohammad Elmekkawy, 2018)
Introduction : Excessive daytime sleepiness (EDS) is considered the most common sleep-related symptom affecting 20 % of the population and represents a major public health problem. The most common cause of EDS in the clinical setting is obstructive sleep apnea (OSA). Normal sufficient sleep is essential for sound cognitive functions in the subjects.Purpose: This study aimed to the electrophysiological assessment of cognition and sleepiness, in patients suffering from excessive daytime sleepiness (EDS) and finding the correlation between them; (the electrophysiological tools used in cognition and EDS assessment), aiming at potential integration of these electrophysiological tests as diagnostic tools for cognition and EDS.Methods: Forty subjects participated in the study, were divided into two groups: a case group (twenty patients) and a control group (twenty subjects). All participants were subjected to complete clinical evaluation in addition to sleepiness and cognitive assessment using Epworth sleepiness scale (ESS), Mini-Mental State Examination (MMSE), Polysomnography (PSG) once, while Karolinska sleepiness scale (KSS), Trail Making Test (TMTA&B), P300, QEEG were done before and after sleep.Results: The case group showed a statistically highly significant more prolonged P300 (Cz) latency and reaction time (RT) (P <0.001), in addition to reduction of average absolute power (oV2) of occipital alpha (P <0.025) and central (Cz) and temporal delta (p=0.044) after sleep than values before it. Also there was significant positive correlation between the difference of average occipital (O) alpha with (ESS) and with (KSS before sleep).Conclusion: Patients with EDS have electrophysiologic evidence of cognitive affection, as assessed by P300 and QEEG. This finding runs with the suggestion of the use of QEEG as objective tool for sleepiness and cognitive assessment especially when recorded before and after sleep
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Neurophysiology
Issued also as CD
Keywords: Cognition{u2013}Quantitative; Excessive daytime sleepiness (EDS); Obstructive sleep apnea (OSA)